Postoperative residual neuromuscular block in a woman with severe preeclampsia treated with magnesium sulfate and nicardipine: A case report and literature review - Song, Yingcai; Qian, Xiaozhe; Du, Weijia (Frontiers in Surgery, 2023)
Most women with severe maternal hypertension have preeclampsia and are treated with magnesium sulfate and nicardipine. A review of the literature showed delayed neuromuscular blockade after treatment with magnesium sulfate. Since magnesium and calcium have opposite effects on the neuromuscular junctions, muscle weakness may become a postoperative manifestation of magnesium sulfate and calcium antagonist treatment in the obstetric population; however, limited information is available regarding this postulation. Here, we report a case wherein rocuronium activity was markedly prolonged due to pretreatment with magnesium sulfate and nicardipine after general anesthesia during an emergency cesarean delivery.